2020
DOI: 10.1002/jlb.5bt0420-585rr
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough concepts in immune-oncology: Cancer vaccines at the bedside

Abstract: Clinical approval of the immune checkpoint blockade (ICB) agents for multiple cancer types has reinvigorated the long-standing work on cancer vaccines. In the pre-ICB era, clinical efforts focused on the Ag, the adjuvants, the formulation, and the mode of delivery. These translational efforts on therapeutic vaccines range from cell-based (e.g., dendritic cells vaccine Sipuleucel-T) to DNA/RNA-based platforms with various formulations (liposome), vectors (Listeria monocytogenes), or modes of delivery (intratumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 395 publications
(661 reference statements)
0
9
0
1
Order By: Relevance
“…Tumor cells vary from foreign germs in that their specific protein immunogenicity is low ( 22 ), the process of tumor immune evasion is complex, and the immune system has a hard time recognizing them ( 23 , 24 ). To accomplish the tumor immune killing effect, a viable technique is to locate suitable tumor-specific peptide epitopes and activate the immune response using adequate immune adjuvants ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells vary from foreign germs in that their specific protein immunogenicity is low ( 22 ), the process of tumor immune evasion is complex, and the immune system has a hard time recognizing them ( 23 , 24 ). To accomplish the tumor immune killing effect, a viable technique is to locate suitable tumor-specific peptide epitopes and activate the immune response using adequate immune adjuvants ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this delivery system, the cytotoxic T lymphocyte responses can be enhanced and less DNA is required in different experimental settings [ 65 ]. Numerous convincing evidence have demonstrated that the antitumor effects of cancer vaccines can be enhanced by gene gun delivery against various cancers such as lung cancer [ 66 , 67 , 68 , 69 , 70 , 71 ]. In spite of this significance, electroporation or gene-gun-based delivery suffer some drawbacks, such as causing considerable pain on administration and not being suitable for community-wide vaccination [ 63 ].…”
Section: Dna Vaccine Delivery Platformsmentioning
confidence: 99%
“…The nomenclature of antigens presented on tumor cells has a long history. To optimize these antigens generally involves HLA ligands, which might be qualified as tumor-associated to be expressed on general tumor cells or on remaining tumor-specific cells 30 . Because tumor-specific neoantigens are usually rejected by malignant cells, they are specifically designed for cancer vaccines 31 .…”
Section: Tumor Antigensmentioning
confidence: 99%